Music - Dewey, Ione (My University, 1893)
Introduction: Music, in some form, has probably existed ever since the world began. The earliest music that we have any record of was the song that was sung by Moses and the Israelites after the passage of the Red Sea, when Miriam took a trimbrel in her hand and answered them. But is must have existed before, though probably not made with instruments. Could anyone doubt that our first mother, in putting her child to sleep, sang to it some sort of lullaby? The world is now and always has been too full of musical sounds to deny it.
Citation: Dewey, Ione. Music. Senior thesis, Kansas State Agricultural College, 1893.
Morse Department of Special Collections
Keywords: Music; Moses; Isrealites; Red Sea; Miriam; Theses; Manuscripts (documents)